The XChemExplorer graphical workflow tool for routine or large‐scale protein–ligand structure determination. Issue 3 (1st March 2017) - Krojer, Tobias; Talon, Romain; Pearce, Nicholas; Collins, Patrick; Douangamath, Alice; Brandao-Neto, Jose; Dias, Alexandre; Marsden, Brian; von Delft, Frank
Abstract : XChemExplorer is a graphical workflow and data‐management tool for the parallel determination of protein–ligand complexes. Its implementation, usage and application are described here. Abstract : XChemExplorer ( XCE ) is a data‐management and workflow tool to support large‐scale simultaneous analysis of protein–ligand complexes during structure‐based ligand discovery (SBLD). The user interfaces of established crystallographic software packages such as CCP 4 [Winn et al. (2011), Acta Cryst. D67, 235–242] or PHENIX [Adams et al. (2010), Acta Cryst. D66, 213–221] have entrenched the paradigm that a `project' is concerned with solving one structure. This does not hold for SBLD, where many almost identical structures need to be solved and analysed quickly in one batch of work. Functionality to track progress and annotate structures is essential. XCE provides an intuitive graphical user interface which guides the user from data processing, initial map calculation, ligand identification and refinement up until data dissemination. It provides multiple entry points depending on the need of each project, enables batch processing of multiple data sets and records metadata, progress and annotations in an SQLite database. XCE is freely available and works on any Linux and Mac OS X system, and the only dependency is to have the latest version of CCP 4 installed. The design and usage of this tool are described here, and its usefulness is demonstrated in the context of fragment‐screening campaigns at the Diamond Light Source. It is routinely used to analyse projects comprising 1000 data sets or more, and therefore scales well to even very large ligand‐design projects.